3000 yr-old patterns of mobile pastoralism revealed by multiple isotopes and radiocarbon dating of ancient horses from the Mongolian Altai - Antoine Zazzo; Maël Le Corre; Nicolas Lazzerini; Charlotte Marchina; Noost Bayarkhuu; Vincent Bernard; Mathilde Cervel; Denis Fiorillo; Dominique Joly; Michel Lemoine; Philippe Telouk; François Thil; et al. (PLoS ONE, 2025)
Pastoral nomadism is of great cultural and economic importance in several regions of the world today. However, documenting ancient patterns of mobility in societies where pastoralism was central is challenging and requires tailored approaches and methodologies. Here we use strontium, oxygen and carbon isotopic analyses of dental enamel, together with a local strontium isoscape, to reconstruct the mobility patterns of seven domestic horses deposited in a Late Bronze Age grave from western Mongolia. Radiocarbon indicates that the animals were deposited within a short period of time, 3000 years ago. The isotope time series obtained from tooth enamel shows that four of the seven horses exhibited a common pattern characterized by a high frequency of mobility, suggesting that in this area (1) cyclical pastoral mobility dates back at least to the Late Bronze Age and (2) the animals belonged to the same herding family, implying that only a small community was involved in the funerary rite of this structure. The data show that the other three horse individuals had a distinct mobility pattern and that one was not from the local area, pointing to flexibility in mobility patterns over time or circulation of animals between herding groups. These results illustrate the power of the isotopic approach to reconstruct animal biographies and effectively address the archaeology of pastoral nomadism and mobility.